THE EFFECT OF Fe2+ DAN Mn2+ IONS TOWARD β-CAROTENE PRODUCTIVITY BY PHYTOPLANKTON Isochrysis aff galbana (T-iso) - Erna Mayasari; Indah Raya; Hasnah Natsir (Marina Chimica Acta, 2012)
The research aimed to find out the effect of Fe2+ and Mn2+ towards β-carotene productivity as result of oxidative stress from photosystem (PS II). The phytoplanton Isocrysis aff galbana (T-iso) were the microalgae species which had the high lipid content primarily and had potentiality to produce β-carotene as the β-carotene supplement. Analysis method was carried out by the sonication extraction for short and cheap in the lysis cell of phytoplankton biomassa, infra red (IR) to find out the interaction metal ion and UV/VIS spectrophotometer to determine β-carotene concentration. The research result indicateds that Fe2+ has higher impact than Mn2+ on the β-carotene productivity. The interaction of ions metal indicates as   M-N, -O-M and M←OH-C complex in the phytoplankton amino acid. The β-carotene concentration is 4,97 µg/g DW in addition Fe2+ 0,30 ppm and 1,95 μg/g DW in Mn2+  0,20 ppm. The dry weight concentrations of β-carotene indicates that  I. aff galbana with Fe2+ addition has potential as β-carotene supplement.